Relationship between newborn mid-upper-arm circumference and birth weight - Muhammad Anwar Taufiq; Djauriah A. Madjid; J. S. Lisal; Dasril Daud (Indonesian Pediatric Society, 2009)
Background Recording an accurate birth weight by primaryhealth care workers has been a problem in rural areas, leadingto a search for an alternative, inexpensive, age independent andnoninvasive method to predict neonatal well being. Mid-upper-armcircumference (MUAC) might be an alternative anthropometricmeasurement useful to estimate the state of nutrition.Objective To evaluate the relationship between MUAC andbirth weight in low birth weight (LBW) and normal birth weight(NBW) infants.Methods We measured birth weight and MUAC of newbornbabies of various gestational ages at Siti Fatimah Maternity andChildren's Hospital and Dr. Wahidin Sudirohusodo GeneralHospital, Makassar, South Sulawesi, Indonesia. Correlationtests and diagnostic accuracy using different cut-off points wereperformedResults There were 892 live birth newborns (117 LBW and 775NBW) included in the study. The sensitivity, specificity, positivepredictive value, and negative value for MUACs of< 10.3 em were94.9 %, 99.9%, 99.1%, and 99.2%, respectively. The sensitivity,specificity, positive predictive value, and negative value for MUAC< 10.4 em were 99.1 %, 99.6%, 97.5%, and 99.9%, respectively.The sensitivity, specificity, positive predictive value, and negativevalue for MUAC < 10.5 em were 100%,99.4%, 95.9%, and 100%,respectively.Conclusion There is a strong correlation between MUAC andbirth weight. Birth weight can be predicted with the followingequation: Birth weight= -1776.383 + (416.95 newborn MUACvalue). The optimal cut-off point for the newborn MUAC value forLBW infants is< 10.5 em.